George H. Hall papers - Hall, George H.
Diaries (1861-1866) containing Hall's observations of civilian unrest and troop mobilizations in Maryland in the spring of 1861, as well as references to Abraham Lincoln's first inauguration, the Maryland secession convention, and most of the major battles of the Civil War. Also includes a postcard to Hall from his mother pertaining to family matters.
Merchant and postmaster from Maryland.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Inauguration, 1861.; Secession; Maryland -- History -- Civil War, 1861-1865.; Maryland -- Politics and government -- 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Merchants; Postmasters